Prognostic significance of ischemic electrocardiographic changes during stress testing in patients with normal nuclear myocardial perfusion imaging - Ghufran Adnan; Fateh ALi Tipoo Sultan; Umaira Alauddin; Maria Ali Khan (Journal of the Pakistan Medical Association, 2021)
Objectives: The main objective of this study was to evaluate cardiovascular outcome in patients with normal nuclear myocardial perfusion imaging but ischemic ECG changes during pharmacological or exercise stress test. Methods: In this retrospective study, we included a cohort of patients who underwent either pharmacological or exercise stress MPS and have a normal scan with ischemic EKG changes at Aga Khan University Hospital, from January 2013 to December 2014. All cardiac events including angina, myocardial infarction, heart failure, coronary revascularization and cardiac death as well as non-cardiac death were determined for the whole follow up period. Results: Among 2770 eligible patients, 296 patients (10.6%) developed ischemic EKG changes during stress test but myocardial perfusion scan was normal. Out of 296 patients 181(61%) were male and mean age was 61.98 + 15 years. We were able to follow 280 patients (94.5%). During a mean follow-up of 4 years + 7 months, 8 patients (2.8 %) died, of which only one patient (0.3%) died due to cardiac cause. Angina occurred in 25patients (8.9%), myocardial infarction in 2 patients (0.7%) and one patient hospitalized with heart failure (0.3%). We performed coronary angiography of 16 patients (5.7%), of which nine underwent percutaneous transluminal coronary angioplasty (PTCA) and coronary artery bypass grafting (CABG) was done in three patients. Conclusion: The ischemic electrocardiographic changes during stress testing in patients with normal MPI are not associated with poor out come and the risk of cardiovascular events is relatively low for an intermediate follow up period. Continuous....